Surface TLR2 and TLR4 Expression on Mature Rat Mast Cells Can Be Affected by Some Bacterial Components and Proinflammatory Cytokines - Anna Pietrzak; Maciej Wierzbicki; Magdalena Wiktorska; Ewa Brzezińska-Błaszczyk (Hindawi Limited, 2011)
The aim of our study was to determine whether some bacterial components as well as some proinflammatory cytokines can affect surface mast cell levels. By the use of flow cytometry technique, we documented that freshly isolated mature rat peritoneal mast cells do express surface TLR2 and TLR4 protein, but not CD14 molecules, and respond to stimulation with TLR2 and TLR4 ligands by cysteinyl leukotriene generation. The level of TLR2 protein is modulated by PGN and CCL5 treatment, but not by LPS, LAM, TNF, or IL-6. Surface mast cell TLR4 expression is affected by LPS, LAM, IL-6, and CCL5. Considering that TLR-mediated activation conditions not only engaged these cells in antibacterial defense and development of inflammation but also might influence allergic processes, our observations that surface TLR2 and TLR4 expression can be regulated both bacterial components and proinflammatory cytokines seem to be very intriguing and importance.